Relationship between Central Cornea Thickness (CCT) and Intraocular Pressure (IOP) among young Malay adult with hyperopic correction / Nur Filzah Abdul Razak - Abdul Razak, Nur Filzah (Faculty of Health Sciences, 2015)
The purpose of this study is to evaluate the normal value of CCT and IOP among the young Malay adult and also to determine the relationship between CCT and IOP. A cross-sectional study is done among the UiTM Puncak Alam students and staffs. 24 subjects were enrolled in this study which fulfilled all the criteria needed including 17 females and 7 males. They were grouped into two group which were emmetrope and hyperope group. Tomey Specular Microscopy is used to measure CCT while Keeler Air Puff Non Contact Tonometer to measure IOP. The results obtained showed a significance correlation between the CCT and IOP (r=0.316, p=0.03). The mean values of CCT and IOP among hyperopic group are 528.81um (±22.078) and 13.63mmHg (±2.976 mmHg) respectively. The mean values of CCT and IOP in emmetropic group are 538.29um (±24.879um) and 13.194mmHg (±2.2064mmHg) respectively. The correlation of CCT and IOP with the refractive error is poor with r = 0.233 (p = 0.114) and r = 0.142 (p = 0.342) respectively. Thus, it was true that CCT can affect the IOP based on the findings in this study but no significant correlation between refractive error with CCT and IOP.